Model Integrasi Pembelajaran Pondok Pesantren dengan Madrasah Tsanawiyah di Madrasah Tsanawiyah Pondok Pesantren Al Fatah Temboro Magetan - Zikry Septoyadi; Vita Lastriana Candrawati; Fakhrurrozin Al-Asy'ari (At-Tarbawi: Jurnal Kajian Kependidikan Islam, 2021)
This research is motivated by the learning process at MTs AL Fatah Temboro at MTs Al Fatah Temboro which combines pesantren education and formal education. This study aims to describe and analyze the learning integration model of the Al-Fatah Islamic Boarding School Temboro which is located in Magetan. Using a qualitative approach, this study concludes that Al Fatah Islamic boarding school has an important role in improving formal education by combining pesantren education (diniyah) and formal education. This pesantren-based learning process has been carried out since the beginning of the Madrasah until now very well. The integration model used is to combine the curriculum and regulations of the Ministry of Religious affairs which combined with the pesantren curriculum. Al Fatah Islamic Boarding School Temboro modified the learning process along with its methods and strategies without leaving the rules set by the government and the Ministry of Religion.